2005
DOI: 10.1056/nejmp058102
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury in the War Zone

Abstract: a supply officer with a U.S. Army Stryker Brigade, was stationed at a submachine gun on a truck rolling through northern Iraq last November, in a convoy transporting Iraqi volunteers to Mosul for military training. As they entered the town of Talafar, Emme noticed that the streets were unusually quiet: no children were outdoors running toward the vehicles demanding sweets. Emme got on the radio and warned others in the convoy: "Something might happen. They might have some plan for us."Moments later, as they sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
457
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(460 citation statements)
references
References 2 publications
2
457
0
1
Order By: Relevance
“…In one of the largest reviews of mTBI, the WHO task force that reviewed mTBI literature up to 2004 concluded that mTBI research is "of varying quality and causal inferences are often mistakenly drawn from cross-sectional studies (p. 84," (Carroll et al, 2004a), see also (Ragnarsson, 2006) The only correction for this gaffe in the neuropsychology of concussion, and potential long-term sequelae of PPCS, will be large, unbiased prospective studies that address the issues raised in this review. The importance of understanding this more accurately and completely is the fact that concussion is reportedly the most common of all neurological injuries and this is also true of the Iraq and Afghanistan war (Das & Moorthi, 2005;Okie, 2005;Warden, 2006;Warden & French, 2005), where unofficial estimates place the numbers in the tens of thousands (Bob Woodruff Reports. February 27, 2007: www.abc-.com), potentially as high as, "1 out of every 10 returning service men and women" [p. 16, American Academy of Neurology News, 20(6), 2007].…”
Section: Resultsmentioning
confidence: 99%
“…In one of the largest reviews of mTBI, the WHO task force that reviewed mTBI literature up to 2004 concluded that mTBI research is "of varying quality and causal inferences are often mistakenly drawn from cross-sectional studies (p. 84," (Carroll et al, 2004a), see also (Ragnarsson, 2006) The only correction for this gaffe in the neuropsychology of concussion, and potential long-term sequelae of PPCS, will be large, unbiased prospective studies that address the issues raised in this review. The importance of understanding this more accurately and completely is the fact that concussion is reportedly the most common of all neurological injuries and this is also true of the Iraq and Afghanistan war (Das & Moorthi, 2005;Okie, 2005;Warden, 2006;Warden & French, 2005), where unofficial estimates place the numbers in the tens of thousands (Bob Woodruff Reports. February 27, 2007: www.abc-.com), potentially as high as, "1 out of every 10 returning service men and women" [p. 16, American Academy of Neurology News, 20(6), 2007].…”
Section: Resultsmentioning
confidence: 99%
“…The number of TBI casualties, sustained by Coalition Forces engaged in the wars in Afghanistan, Operation Enduring Freedom, and Operation Iraqi Freedom during the past 5 years, indicates that TBI will continue to be a major threat to military personnel in the 21st century. 1,2 According to the Joint Theater Trauma Registry, compiled by the U.S. Army Institute of Surgical Research, 22% of wounded soldiers from Iraq and Afghanistan have injuries of the head, face, or neck, which has substantially increased in comparison with the casualties suffered in the Vietnam War. 3 At least some of this increase in TBI is due to increased survivability, resulting from improvements in body armor and helmet design, and rapid medical intervention.…”
Section: Traumatic Brain Injury: a Global Health Problemmentioning
confidence: 99%
“…Since 2001, more than 2 million troops have deployed to the Global War on Terrorism (GWOT) in AfghanistanDespite improvements that reduce injury and risks of long-term effects from casualties [3][4][5], up to 19 percent of returning servicemembers are thought to have experienced traumatic brain injury (TBI), the "signature injury" of GWOT [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%